'Sleep, baby, sleep' - Awre, Gabrielle; Lynda (The University of Hull, 2017)
This melody has German origins and is probably very old. A version of this tune was composed in 1781 based on an older folk tune and there is another version from 1611 according to Wikipedia (https://en.wikipedia.org/wiki/Schlaf,_Kindlein,_schlaf)